Prabowo Subianto-Sandiaga Uno Grand Campaign 7 April 2019 On Indonesian Presidential Election: Experience of Othering and Online Media - Pardede, Carlos Margondo (UI Scholars Hub, 2020)
Indonesian Presidential Election 2019 sees a rematch between Prabowo Subianto and President Joko Widodo. The threat by intolerant Islamics elements that are deeply rooted within the political mainstream, has not only posed Indonesia’s democratic downturn. Opposition pressure at national level had also contributed to this phenomena. The Jakarta 2017 Gubernatorial election has been the decisive specimen applied in the 2019 Presidential Election. The Presidential election has witnessed the repurpose of the Jakarta Gubernatorial political campaign techniques namely the sectarian mobilisation polarizing the public opinion, and the politics of the religious identity. Prabowo Subianto-Sandiaga Uno Presidential Election Grand Campaign on April 7, 2019, was very different from any other grand campaign on Indonesian election history. Adapting the qualitative methods, the researcher conducted interviews to 4 editors from trusted online media in Indonesia. Media framing and othering are important in this discussion, as it can describe how online media journalists implemented their professional work to cover and deliver the Prabowo Subianto-Sandiaga Uno presidential election grand campaign on April 7, 2019.